ISLAM DAN KEKUASAAN ORDE BARU: Membaca Kembali Politik De-Islamisasi Soeharto - Darma Wijaya (Jurnal Sosiologi Reflektif, 2015)
In 1966 was the beginning of New Order rezim. There was anyone who cannot argue that Moslem people had played an important role in bearing a new order. It was, therefore, natural that Moslem people have very extremely expected to manage this state with many more. This expectation was just imagination, because Suharto, as a leader of new order, did not give space adequately for them. Suharto exactly runs political of deislmatization systematically, in essential for marginalizing for Moslem people. The process reached the climax in 1985, in where the new order issued regulation setting that Pancasila (the fie basic principles of Republic of Indonesia) as a single principle, so this signed the death of Islam as political ideology in Indonesian history.